2006
DOI: 10.1007/s10546-006-9135-8
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Balance Experiment EBEX-2000. Part III: Behaviour and quality of the radiation measurements

Abstract: An important part of the Energy Balance Experiment (EBEX-2000) was the measurement of the net radiation and its components. Since the terrain, an irrigated cotton field, could not be considered homogeneous, radiation measurements were made at nine sites using a variety of radiation instruments, including pyranometers, pyrgeometers and net radiometers. At several of these sites multiple instruments were employed, which enabled us to compare instruments and assess accuracies. At all sites the outgoing longwave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
65
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 13 publications
2
65
1
Order By: Relevance
“…It performed well almost within the accuracy of their reference net radiation that was ±3.5% and ±10 W m −2 (whichever was the largest). Kohsiek et al (2007) found that CNR1 and Schulze-Däke yielded similar values (within 20 W m −2 ) like the reference sum of four components.…”
Section: Radiationmentioning
confidence: 56%
See 4 more Smart Citations
“…It performed well almost within the accuracy of their reference net radiation that was ±3.5% and ±10 W m −2 (whichever was the largest). Kohsiek et al (2007) found that CNR1 and Schulze-Däke yielded similar values (within 20 W m −2 ) like the reference sum of four components.…”
Section: Radiationmentioning
confidence: 56%
“…The measurement of net radiation has been subject of several studies (e.g. Brotzge and Duchon 2000;Duchon and Wilk 1994;Field et al 1992;Halldin and Lindroth 1992;Kohsiek et al 2007;Vogt et al 1996;Vogt 2000). The evaluation of the accuracy of the net radiation measurements is complicated as there is no accepted standard for net radiation measurements (e.g.…”
Section: Net Radiationmentioning
confidence: 99%
See 3 more Smart Citations